PENGARUH GAYA MANAJEMEN TERHADAP KINERJA PERUSAHAAN (Studi Pada Perusahaan Dealer Otomotif di Makassar) - Indrawan Azis (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
The Influence of Management Style Against Performance Company.(Study in company of existing otomotif dealer in Makassar). The purpose of this research is to investigate the effects of this research to know direct influence of Management Style to Performance Company. Using these variables, pursuant to result of former research: Dani Ariadi ( 2006). The study was conducted in some company of existing dealer otomotif in Makassar, data collection is done by using a questionnaire that was delivered directly by the researchers to limit the charging time of the next one week taken by the researchers. Analysis method the used doubled linear regression method, significance test by parsial and in concern of t test and F test. Analysis conducted by using computer program of SPSS version 14,0. From result of research of management style to Company performance show negative so that concluded that Management style don’t have an effect on signifikan to Company performance.